Measuring the quality of airline services: Evidence from Northern Cyprus - Kozak, Nazmi; Karatepe, Osman M.; Avcí, Turgay (Cognizant Communication Corporation inquiries@cognizantcommunication.com 3 Hartsdale Road Elmsford NY 10523-3701, 2003)
This study set out to examine the service quality and customer satisfaction delivered by the national airline company in Northern Cyprus, using a SERVQUAL scale. For this purpose, the translated instrument was purified using an item categorization technique and administered to 270 current users of the national airline company at an international university in the region. The results of the confirmatory factor analysis revealed that the predicted five-dimensional structure of SERVQUAL was partially confirmed by the data. SERVPERF scores gave a better prediction of overall satisfaction and showed almost the same reliability and validity as those from which expectations were subtracted. The largest service gaps were identified with the reliability and responsiveness dimensions, and the smallest with the empathy dimension. Reliability and responsiveness dimensions were found by path analysis to be significant determinants of customer satisfaction. Implications of the results are discussed. © 2003 Cognizant Comm. Corp.
Keywords: Customer satisfaction; Expectations; National airline company; Perceptions; Service quality; SERVPERF; SERVQUAL